Axial flux interior PM synchronous motor: parameters identification and steady-state performance measurements - Cavagnino, A.; Lazzari, M.; Profumo, F.; Tenconi, A. (IEEE transactions on industry applications, 2000)
This paper presents different measurement and identification approaches applied to a nonconventional permanent-magnet (PM) synchronous machine, namely, the novel axial flux interior PM (AFIPM) synchronous motor. The nonconventional geometry of the AFIPM motor requires a dedicated discussion on the parameter identification subject. In the paper, the standstill frequency-response test and the standstill time-response test on the AFIPM prototype are presented. On the basis of these tests, the d- and q-axes circuit parameters are chosen. To confirm the validity of the standstill tests, the load tests have also been performed. Furthermore, the load tests provide some preliminary AFIPM machine performance results and additional information on the saturation phenomena. The d- and q-axes equivalent circuits parameters obtained by the performed measurements are analyzed and compared. Finally, the most appropriate AFIPM machine model is selected.